Psikoedukasi Pendidikan Seksual melalui Kuliah Kerja Nyata (KKN) untuk Meningkatkan Pemahaman dan Sikap Remaja terhadap Pencegahan Kekerasan Seksual di Desa Paseh Kidul : Pengabdian - Salvina Bintan Tazkia; Tasya Augustiya; Linda Nur Rahmawati; Rosiana Dewi; Zahran Rabbani; Nanda Shaumalia Putri; Dinda Hanifah; Ihsan; Ahnaf Musyaffa; Muhammad Zaidan Ilham S; Aline Mumtaz Kurniawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sexual violence is one of the most cruel forms of human rights violations, especially against women and children. In Indonesia, there has been an increase in cases of sexual violence, often occurring in public spaces that are supposed to be safe, such as schools. The main factor causing the prevalence of sexual violence is the low level of understanding of sexuality education among adolescents, which has the potential to trigger promiscuity and other negative behaviors. The purpose of this study was to increase the understanding of adolescents in Paseh Kidul Village regarding sexuality education through the application of the psychoeducation method with a pretest-posttest design. Psychoeducation was implemented for adolescents in Paseh Kidul Village, particularly at SMPN 2 Paseh, involving 213 students using interactive modules and discussions to deliver the material comprehensively. This study found that there was a significant increase in adolescents' knowledge after the intervention, where adolescents' understanding of sexuality education increased from 15% in the pretest to 80% in the posttest. Psychoeducation has been proven to be effective in changing adolescents' views on sexuality and encouraging the formation of positive attitudes to maintain physical and psychological health, as well as preventing sexual violence and promiscuity. This study emphasizes the urgency of sexuality education from an early age as an effort to prevent problems and build healthy character in adolescents.